The millipede genus Julus Linnaeus, 1758 in the Caucasus (Diplopoda: Julida: Julidae) - Evsyukov, Aleksandr; Golovatch, Sergei; Reip, Hans S. (Zootaxa, 2018)
The genus Julus includes seven species already described from the Caucasus region: J. alexandrae Evsyukov, 2016; J. colchicus Lohmander, 1936; J. jedryczkowskii Golovatch, 1981; J. kubanus Verhoeff, 1921; J. lignaui Verhoeff, 1910; J. lindholmi Lohmander, 1936; and J. subalpinus Lohmander, 1936, as well as two new species: J. khostensis sp. n., from the Krasnodar Province, and, J. dagestanus sp. n., from the Republic of Dagestan, both in Russia. All nine species are described, illustrated and keyed, their morphological variations outlined, and distributions mapped, based on the literature data and abundant new samples. Altitudinal distribution patterns are also discussed.